Effect of the Er, Cr: YSGG Laser Parameters on Shear Bond Strength and Microstructure on Human Dentin Surface - Rhim, Eun Mi; Huh, Sungyoon; Kim, Duck Su; Kim, Sun-Young; Ahn, Su-Jin; Kang, Kyung Lhi; Park, Sang Hyuk (IntechOpen, 2011)
None